Sero-prevalence and Risk Factors Associated with Bovine Brucellosis in Central Equatoria State, South Sudan - Lita, Emmanuel P.; Nasinyama, George W.; Ochi, Erneo B.; Bugeza, James; Erume, Joseph (Scholars Journals of Agriculture and Veterinary Science, 2016)
Brucellosis is one of the most important zoonotic diseases of livestock and human in South Sudan. A cross sectional study was conducted in peri-urban Juba town and rural Terekeka County to estimate sero-prevalence and determine risk factors of bovine brucellosis. Ninety (90) respondents were randomly interviewed on demographic information and potential risk factors to brucellosis. Out of the 90 respondents interviewed, 44 were from 44 cattle herds in peri-urban Juba and 46 from 46 cattle herds in rural Terekeka County. Sera of 502 cattle were screened for Brucella antibodies using Rose Bengal Plate test. The positive sera on RBPT were then confirmed by competitive Enzyme-linked Immunosorbent Assay. SPSS version-18 and frequencies were used for sero-prevalence. Chi square and binomial logistic regressions were used for analysis of risk factors. RBPT and c-ELISA tests showed positive reactors and an overall individual animal sero-prevalence of 23.2%, 95% confidence interval (CI): (18.4 - 28.8) and 19.2%, 95% CI: (2.5 – 14.0), respectively in peri-urban Juba town. However, in rural Terekeka County the respective results showed seroprevalence of 40.5%, 95% CI: (34.5 – 46.4) and 39.3%, 95% CI: (33.3– 45.2). The overall herd level sero-prevalence on c-ELISA revealed 61.4% and 90.0% for peri-urban Juba town and rural Terekeka County cattle herds, respectively. The individual animal level risk factors in the study area revealed abortion history (OR= 4.941 and (CI): 2.077-11.753) and (OR= 6.251 and (CI): 2.920-13.379) significantly associated with brucella sero-positivity, respectively. No risk factor determined at herd level in peri-urban Juba town. However, in rural Terekeka County herds, number of cattle above 300 in a herd (p= 0.005, OR= 44.934) was significantly associated with brucellosis sero-positivity. Further epidemiological studies are needed for developing appropriate control strategies against bovine brucellosis in South Sudan.